Effektiewe bestuur op die onderleidingvlak - F. W. Marx (South African Journal of Business Management, 1983)
– Effective management at the lower level It is essential that the productivity performance of the South African worker be improved considerably. It is believed that lower management, being in the position of direct supervisors of the low level workforce, can make an important contribution in this direction. Effective management at the lower level, however, requires thorough training in order to make the supervisor aware of the technical and especially the human requirements of his difficult task. A recent survey has revealed that South African companies are not using motivation theories and teaching methods to a large extent in respect of lower management. It appears, therefore, that effective management at the lower level is not receiving sufficient attention.The difficult task of the supervisor is elucidated and several suggestions given for furthering effective management at the lower level.
Keywords: 650